Memorandum of Understanding between the University of Sussex of Falmer and Institute of Educational development, BRAC University (2006) - The University of Sussex; Institute of Educational Development, BRAC University (The University of Sussex and Institute of Education Development, BRAC University, 2013)
This agreement dated 20th January, 2006 is made between: 1. The University of Sussex whose principal administrative office is at Sussex House, Falmer, Brighton BN1 9RH, United Kingdom (the "University"): and BRAC University Institute of Educational Development (BU-IED) whose principal administrative office is at 113/A, Road-2, Niketon Housing, Gulshan-1, Dhaka-1212, Bangladesh (the "Sub-contractor").